Halal Space and Culinary Tourism of Hong Kong: A Guide for Muslim Travelers - Ahmadin, Mr. (Rayhan Intermedia, 2024)
This article discusses my personal experience as a Muslim traveler visiting several attractions, public spaces, and restaurants in Hong Kong City from late October to early November 2017. The narrative of this experience aims to serve as a guide and reference for other Muslim travelers who will visit the country. The approach of this study uses the perspective of sociology of space by using qualitative data both in description and analysis. Data collection techniques were carried out in the form of direct observation and recording, interviews with tour guides, and documentation. The results showed that the Hong Kong government has an interesting tourism sector policy, including the provision of various culinary tourism destinations and some of them are restaurants that provide halal menus. This can be seen as a spatial awareness and spatial practice, especially in the field of urban tourism. The practical benefit of the study is as a guide for Muslim tourists who will visit Hong Kong.